Integrated multi-omics analysis reveals the involvement of the gut-brain axis in children with autism - Zhong, Hongping; Zhang, Shuyue; Mou, Zichao; Fan, Xiaojing; Zhang, Xiayue; Wang, Lixia; Xu, Xijia; Xue, Xinxin; Yang, Fan; Shu, Jianbo; Wang, Mingbang; Cai, Chunquan (Frontiers in Microbiology, 2026)
BackgroundAutism Spectrum Disorder (ASD) is frequently accompanied by gastrointestinal (GI) comorbidities and gut microbiota dysbiosis. While the microbiota-gut-brain axis is implicated in ASD pathophysiology, the upstream host genetic factors that drive these specific microbial alterations remain poorly characterized.MethodsTo bridge this gap, we performed an integrated multi-omics analysis combining whole-exome sequencing, 16S rRNA gene sequencing, and plasma metabolomics in a cohort of children with ASD and typically developing controls.ResultsWe confirmed that children with ASD exhibit significant gut microbial dysbiosis and metabolic perturbations, which correlated with GI symptom severity. Crucially, rare variant enrichment analysis identified a significant accumulation of deleterious variants in mucin biosynthesis pathways (specifically the MUC gene family), which are essential for intestinal mucus barrier integrity. Multi-omics integration revealed that these host genetic defects were associated with distinct shifts in the gut ecosystem, notably the depletion of beneficial butyrate-producing bacteria (e.g., Faecalibacterium) and the expansion of mucin-degrading taxa. This structural dysbiosis translated into functional metabolic impairments, particularly in lipid transport and short-chain fatty acid metabolism, which tracked with ASD severity.ConclusionCollectively, our data argue for a host-centric cascade where genetic vulnerabilities-specifically within the MUC pathway-compromise mucosal integrity, acting as a selective filter that fundamentally reshapes the gut microbiome. By pinpointing these variants as upstream drivers of gut-brain axis dysfunction, we move beyond simple association to identify concrete genetic targets-rare deleterious variants in the mucin (MUC) gene family-for future precision interventions in ASD.